2020
DOI: 10.3390/ma13235362
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Structural and Energetic Differences between Conformations of the SARS-CoV-2 Spike Protein

Abstract: The novel coronavirus disease 2019 (COVID-19) pandemic has disrupted modern societies and their economies. The resurgence in COVID-19 cases as part of the second wave is observed across Europe and the Americas. The scientific response has enabled a complete structural characterization of the Severe Acute Respiratory Syndrome—novel Coronavirus 2 (SARS-CoV-2). Among the most relevant proteins required by the novel coronavirus to facilitate the cell entry mechanism is the spike protein. This protein possesses a r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 64 publications
0
44
0
Order By: Relevance
“…The RBD/S1 (~200 amino acids) of S protein undergoes down-to-up conformational transition during interaction with membrane bound ACE2 recepetor, facilitating cell recognition and binding. In addition, RBD substantially contributes towards the overall mechanical stability of homotrimeric spike [14]. The S2 subunit with its fusion peptide (FP), central helix (CH), connecting domain (CD), heptad repeat (HR1/2) domain mediates integration between viral and host cell membrane.…”
Section: Description Of Structural Proteinsmentioning
confidence: 99%
“…The RBD/S1 (~200 amino acids) of S protein undergoes down-to-up conformational transition during interaction with membrane bound ACE2 recepetor, facilitating cell recognition and binding. In addition, RBD substantially contributes towards the overall mechanical stability of homotrimeric spike [14]. The S2 subunit with its fusion peptide (FP), central helix (CH), connecting domain (CD), heptad repeat (HR1/2) domain mediates integration between viral and host cell membrane.…”
Section: Description Of Structural Proteinsmentioning
confidence: 99%
“…While SARS-CoV-1 requires cleavage of the S protein at the S1/S2 site by host proteases in the entry steps, the S1/S2 site of the S protein of SARS-CoV-2 is cleaved by intracellular protease furin in the viral assembly step, which may affect the cell tropism and the entry efficiency of SARS-CoV-2 [ 13 ]. In addition, it is suggested that the stability and glycosylation state of the S protein regulates its conformations to maintain the contact with ACE2 receptor, which is also related to vital entry efficiency [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 20 , 23 , 24 , 25 , 26 , 27 ]. More recently, Acetylcysteine has been used in the development of therapies for respiratory infections such as influenza and COVID-19 [ 28 , 29 , 30 ], where the integrity of the spike protein is vital for infection [ 12 , 13 ]. A hypothesized mechanism of action could be the unfolding of the spike glycoprotein and the reduction of its disulfide bonds.…”
Section: Discussionmentioning
confidence: 99%
“…The entry of viruses into mammalian cells, or “virus internalization”, is a key mechanism of enveloped virus infection and is based on dynamic conformational changes of their surface glycoproteins, namely, as mediated by disulfide bond reduction and regulated by cell surface oxydoreductases and proteases [ 5 , 8 , 9 , 10 , 11 ]. SARS-CoV-2 entry into host cells has been shown to start with destabilization of the spike protein through allosteric mechanical transition, which induces a conformational change from the closed “down” state to open “up” state of the receptor binding domain (RBD) of the spike protein [ 12 , 13 ]. The conformational changes of RBD and virus binding are induced by TMPRSS2 or Cathepsin L, which trigger the transition from the pre-fusion to post-fusion state [ 5 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation